Navigating Through The Diagnostic and Management Maze of Atypical Optic Neuritis Due To Autoimmune: Poster Presentation - Case Report - Resident - Andi Marsa Nadhira; Syntia Nusanti; Salmarezka Dewiputri; Sita Paramita; Muhammad Sidik (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Typical and atypical optic neuritis (ON) have many overlapping characteristics; however, atypical ON have different features, with more lasting visual impairment and devastating prognosis. This paper describes a challenging case of recurrent, atypical ON due to autoimmune. Case Illustration : 42-year-old female complained of recurrent attacks of bilateral blurry vision, eye pain, and headachefor the past two years. Patient had been on multiple rounds of high-dose oral methylprednisolone, but symptoms reappeared every time it was tapered down. Visual acuity of both eyes was 3/60 and 6/45 (without and with correction, respectively), with normal intraocular pressure, anterior and posterior segment, and cranial nerves. No relative afferent pupillary defect was present. Brain magnetic resonance imaging (MRI) revealed intracerebral chronic small vessels; with no lesion in both optic nerves nor signs of neuromyelitis optica. Blood work-up showed elevated C-reactive protein, platelet aggregation, fibrinogen, D-dimer; positive rheumatoid factor, antinuclear antibody, and lupus anticoagulant; and negative Aquaporin-4 IgG. Diagnosis of atypical ON was established. Internal medicine and neurology departments diagnosed her with non-radiographic axial spondyloarthritis and migraine due to attributed autoimmune, respectively. After administration of intravenous pulse dose of methylprednisolone, her vision recovered to 6/7,5 of both eyes and symptoms alleviated. Discussion : Atypical features usually give hints for atypical ON, while laboratory examination and imaging modalities may aid in etiology identification. Early immunosuppressant therapy is commonly required. Conclusion : Recognizing symptoms of ON and necessitating further evaluation through ancillary tests, and collaborations with other specialties can minimize long-lived ailment and improve patients’ quality of life.